PENGARUH OPINION SHOPPING DAN FINANCIAL DISTRESS TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Hanna Elisabeth; Khalida Utami; Nelyumna (Jurnal Ilmiah Akuntansi Pancasila (JIAP), 2026)
The purpose of this study is to provide empirical evidence regarding the effect of opinion shopping and financialdistress on the acceptance of going concern audit opinions in property and real estate companies listed on theIndonesia Stock Exchange from 2019 to 2023. The sample was selected using purposive sampling, which resultedin 25 property and real estate companies that met the specified criteria. Hypothesis testing was conducted usinglogistic regression techniques with the assistance of SPSS version 27. The results showed that the practice ofopinion shopping had a significant negative effect on the acceptance of going concern audit opinions; meanwhile,financial distress had no significant effect on the acceptance of going concern audit opinions.